﻿Checklist, distribution, diversity, and rarity of mayflies (Ephemeroptera) in Slovakia - Macko, Patrik; Derka, Tomáš; Šamulková, Michaela; Novikmec, Milan; Svitok, Marek (ZooKeys, 2023)
Despite the essential role of mayflies (Ephemeroptera) in freshwater ecosystems and their long-term use in research and routine biomonitoring in the Carpathian and Pannonian ecoregions, their distribution data are fragmentary and outdated. All published and unpublished data on mayflies from Slovakia was gathered and a database of > 15,000 species records from 2206 localities built with the aims (i) to critically revise available data and assess the completeness of the species inventory, (ii) to identify hotspots of species diversity, and (iii) to provide a benchmark for assessment of species rarity and conservation status in the region. After the critical revision of the data covering more than 100 years, the occurrence of 109 mayfly species in Slovakia was confirmed. The species inventory appears to be nearly complete, as evidenced by the rarefaction curve and a nonparametric species richness estimator. The highest mayfly gamma diversity was recorded below 500 m a.s.l. and in streams of the fifth order, which can be considered hotspots of mayfly diversity in the region. Six species were last recorded before 1990 and thus can be considered extinct in Slovakia. Twenty-nine species could be classified as very rare, with their occurrence frequency decreasing with increasing altitude and most of them being restricted to large lowland rivers and stagnant water habitats in their floodplains. In conclusion, our study provides comprehensive data on key freshwater bioindicators and suggests increasing conservation priorities, especially in lowland river floodplains occupied by several very rare mayfly species.
Keywords: lowland rivers; rare taxa; species richness; Freshwater bioindicators; species frequency